Creative clusters in low density urban areas: A case study approach - Catarina Selada; Ines Vilhena Da Cunha; Elisabete Tomaz (European Regional Science Association (ERSA), 2010)
Creative clusters are considered to be only viable in big cities. However, creativity can act as a driving force for the development of low density areas, combating the exodus to large metropolis. On one hand, creative people are attracted to low density environments characterized by the presence of endogenous assets, such as natural and historical-cultural amenities and by a healthy quality of life. On the other, creative businesses in the areas of design, crafts, arts, etc are the result of an active entrepreneurial spirit of these talented people who want to live, work, learn and play in these creative communities. Places with a higher concentration of creative occupations tend to have more creative activities and to develop dynamic creative clusters. Furthermore, creative industries provide innovative inputs and knowledge spillovers to traditional sectors of small economies. Thus, the creative issue could contribute to impulse a sort of leapfrog in terms of social and economic development for small and midsize towns as well as an excellent opportunity to rethink rural development. Local public policies have a role to fulfill, promoting strategies oriented to: attraction of the creative class; enhancement of creative entrepreneurship; promotion of creative industries; creation of artistic and cultural infrastructures (museums, galleries, schools, incubators); launching of events, fairs and exhibitions; promotion of creative urban regeneration, etc. But, the presence and role of creative clusters and talents in low density zones need to be more widely acknowledged in order to pursue innovation policies aimed at developing small economies. The objective of this paper is to contribute to a better understanding of the relationship between low density areas and the development of creative industries and the attraction of talented people. The research approach will be based on a case study methodology centered on the analysis of three European examples of creative small urban environments (Óbidos, PT; Barnsley, UK; Hódmez√µvásárhely, HU). A conceptual model and a set of analysis dimensions will be defined as the theoretical background of this benchmarking exercise. The aim of this investigation is to distil best practices and policy recommendations for the development of creative low density communities.
Keywords: 330